2019
DOI: 10.1016/j.ebiom.2019.10.018
|View full text |Cite
|
Sign up to set email alerts
|

EHD1 impairs decidualization by regulating the Wnt4/β-catenin signaling pathway in recurrent implantation failure

Abstract: a b s t r a c tBackground: Recurrent implantation failure (RIF) remains a critical and challenging problem in assisted reproductive technology mainly due to impaired decidualization. The endocytic and transcytotic activity in the endometrium are crucial for decidualization. The most representative endocytic gene is the Cterminal Eps15 homology domain-containing 1 (EHD1), but whether EHD1-mediated endocytic function is responsible for embryo implantation during decidualization remains unclear. Methods: A transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…Among these factors, poor endometrial receptivity is the main cause for RIF (Timeva et al, 2014;Vlachadis et al, 2014;Craciunas et al, 2019). There have been researches using either microarray technology or to identify the transcriptomic signature of endometrial samples from RIF patients (Mahajan, 2015;Zhou et al, 2019). However, the pathogenesis of poor endometrial receptivity in RIF cases has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, poor endometrial receptivity is the main cause for RIF (Timeva et al, 2014;Vlachadis et al, 2014;Craciunas et al, 2019). There have been researches using either microarray technology or to identify the transcriptomic signature of endometrial samples from RIF patients (Mahajan, 2015;Zhou et al, 2019). However, the pathogenesis of poor endometrial receptivity in RIF cases has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The endometrium is receptive to implantation during WOI phase, which requires epithelial cells develop specialized structures known as pinopodes secreting cell adhesion molecules and stromal cells initiates decidual reactions providing a nutritive and immunoprivileged matrix essential for embryo implantation ( Lessey and Young, 2019 ). Recent years, there has been increased lines of evidence demonstrating that RIF patients suffered from impaired endometrial decidualization ( Huang C. et al, 2017 ; Szwarc et al, 2019 ; Zhou et al, 2019 ). Our results also showed that ESCs isolated from RIF patients had a poor response to artificial induced decidualization, manifested by the reduced expression of two decidual markers.…”
Section: Discussionmentioning
confidence: 99%
“…The RIF group consisted of patients who had undergone three or more previous failed cycles with at least four morphologically high-grade embryos, but failed to conceive in which there was no other explanation after a through infertility work-up ( Ruiz-Alonso et al, 2013 ; Polanski et al, 2014 ; Bashiri et al, 2018 ; Zhou et al, 2019 ). The control (CTRL) group was women who underwent IVF treatment due to tubal factor infertility, and were able to successfully conceive in first transplantation cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the factors that attributes to RIF; unreceptive endometrium, poor embryos, and unsynchronized maternal-fetal crosstalk; defects in endometrial receptivity accounts for the half of implantation failures in women suffering from RIF after embryo transfer 11,12 . Although there have been extensive studies to identify the multi-omic signatures of endometrium of women with RIF compared to normal women [13][14][15] , pathophysiological features of the endometrium with poor receptivity have not been fully elucidated yet.…”
mentioning
confidence: 99%